Basic College Mathematics (10th Edition)

Published by Pearson
ISBN 10: 0134467795
ISBN 13: 978-0-13446-779-5

Chapter 9 - Basic Algebra - Mixed Review Exercises - Page 700: 22



Work Step by Step

We are given the equation $6(t+3)=-2+20$. In order to solve, we must first use the distributive property to simplify the left side. $6(t+3)=6(t)+6(3)=6t+18=-2+20$ Next, we can combine like terms on the right side. $6t+18=-2+20=18$ Subtract 18 from both sides. $6t+18-18=18-18$ $6t=0$ Divide both sides by 6. $\frac{6t}{6}=\frac{0}{6}$ Therefore, $t=0$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.